Influence of rapid annealing temperature on the mechanical properties of TiCN thin film as prepared by cathodic arc - Phae-ngam, Wuttichai; Gitgeatpong, Ganatee; Prathumsit, Jedsada; Tapanwong, Viboon; Nakajima, Hideki; Chaikeeree, Tanapoj; White, Pattarinee (Creative Science, 2025)
In this study, titanium carbonitride (TiCN) thin films were deposited using cathodic arc deposition techniques. The as-deposited TiCN thin films were subsequently subjected to annealing treatment by rapid thermal annealing (RTA) technique at a temperature range from 400 to 600 °C. The effect of RTA temperature on the crystallinity, morphology, chemical composition, and mechanical properties of the TiCN thin films was investigated. The grazing incident X-ray diffraction (GIXRD) analysis confirmed the presence of a dominant face-centered cubic TiCN phase. Cross-sectional field-emission scanning electron microscopy (FE-SEM) images revealed a compact and homogeneous morphology, which became more pronounced with increasing RTA temperatures. The X-ray photoelectron spectroscopy (XPS) indicated the atomic concentration of the primary element (Ti, C, and N) remained relatively stable throughout the annealing process. Furthermore, the hardness of the TiCN thin films improved at 400 °C-RTA temperature. GRAPHICAL ABSTRACT HIGHLIGHTS Crystalline TiCN thin films were successfully deposited via cathodic arc deposition. RTA treatment improved the TiCN thin film, resulting in a highly compact morphology. The harness of TiCN showed enhancement at 400 oC-RTA temperature.